Towards a Systemic Theory of Irregular Migration Explaining Ecuadorian Irregular Migration in Amsterdam and Madrid - Echeverría, Gabriel (IMISCOE Research Series, 2020)
This open access book provides an alternative theoretical framework of irregular migration that allows to overcome many of the contradictions and theoretical impasses displayed by the majority of approaches in current literature. The analytical framework allows moving from an interpretation biased by methodological nationalism, to a more general systemic interpretation. It explains irregular migration as a structural phenomenon or contemporary society, and why state policies are greatly ineffective in their attempt to control irregular migration. It also explains irregular migration as a diversified phenomenon that relates to the social characteristics of the context, and why states accept irregular migrants. By providing new comparative, empirical, qualitative material which allows to start filling an evident gap in the current research on irregular migration, this book is of interest to graduate students, scholars and policy makers.